Ganglionic Long-Term Potentiation in Prehypertensive and Hypertensive Stages of Spontaneously Hypertensive Rats Depends on GABA Modulation - Luis A. Martínez; Fredy Cifuentes; Miguel A. Morales (Neural Plasticity)
The sympathetic nervous system (SNS) regulates body functions in normal and pathological conditions and is characterized by the presence of a neuroplastic phenomenon, termed ganglionic long-term potentiation (gLTP). In hypertension, either in spontaneously hypertensive rats (SHR) or in humans, sympathetic hyperfunction, such as elevated SNS outflow and changes in synaptic plasticity have been described. Because enhanced SNS outflow is detected in the hypertensive stage and, more importantly, in the prehypertensive phase of SHR, here we explored whether synaptic plasticity, particularly gLTP, was modified in the superior cervical ganglia (SCG) of prehypertensive SHR. Furthermore, considering that GABA modulates sympathetic synaptic transmission and gLTP in Wistar rats, we studied whether GABA might modulate gLTP expression in SHR. We characterized gLTP in the SCG of young prehypertensive 6-week-old (wo) and adult hypertensive (12 wo) SHR and in the SCG of Wistar Kyoto (WKy) normotensive control rats of the same ages. We found that gLTP was expressed in 6 wo SHR, but not in 12 wo rats. By contrast, in WKy, gLTP was expressed in 12 wo, but not in 6 wo rats. We also found that gLTP depends on GABA modulation, as blockade of GABA-A subtype receptors with its antagonist bicuculline unmasked gLTP expression in adult SHR and young WKy. We propose that (1) activity-dependent changes in synaptic efficacy are altered not only during hypertension but also before its onset and (2) GABA may play a modulatory role in the changes in synaptic plasticity in SHR, because the blockade of GABA-A receptors unmasked the expression of gLTP. These early changes in neuroplasticity and GABA modulation of gLTP could be part of the sympathetic hyperfunction observed in hypertension.